Distribution of Heterogeneous, Highly Impure Soy Material in a Deep Air Channel - M. N. Moskovskiy; S. I. Borzenko (Сельскохозяйственные машины и технологии)
The paper highlights a lack of machines and equipment capable of cleaning highly impure soybean material efficiently and productively. Most of the existing grain cleaning machines are designed for the materials conforming to GOST 17109-88 that specifies weed and oilseed impurity contents of 2 and 6 percent, respectively. In reality, a typical soybean post-harvest waste often contains 20 to 60 percent of material unsuitable for extracting raw protein, that makes this type of material completely non–separable for this type of machine. (Research purpose) The research aims to determine the optimal efficiency of separating heterogeneous bulk mixtures in a vertically ascending air channel. (Materials and methods) To accomplish this, the authors employed a rotary batch classifier RBK 30 and a prototype sample of a precision air classifier PAC with column air flow accelerators. The paper defines impurity separation completeness and soybean waste separation efficiency in a novel pneumatic classifier, considering the accelerator thickness and the height above the processed material. (Results and discussion) The findings reveal that traditional pneumatic channels achieve no more than 20 percent of separation efficiency for highly impure soybean material, while the precision air classifier demonstrates approximately a 45 percent separation. (Conclusions) Typical air flow machines struggle with high impurity of material. The separation efficiency of highly impure material can be enhanced by equalizing the air flow velocity inside and above the layer of the separated material and installing a core air flow accelerator. The study indicates that the material being processed can be separated by air flow, provided a specialized pneumatic separation channel is used. Due to the ratio of the core accelerator height and the height above the material, the air flow velocity inside and above the separated layer is equalized.